Prevalence of Pompe disease in 3, 076 patients with hyperCKemia and limb-girdle muscular weakness. (19th July 2016) - Lukacs, Zoltan; Nieves Cobos, Paulina; Wenninger, Stephan; Willis, Tracey A.; Guglieri, Michela; Roberts, Marc; Quinlivan, Rosaline; Hilton-Jones, David; Evangelista, Teresinha; Zierz, Stephan; Schlotter-Weigel, Beate; Walter, Maggie C.; et al.
Abstract : Objective: We prospectively screened a large European cohort of patients presenting with hyperCKemia and/or limb-girdle muscular weakness (LGMW) for acid α-glucosidase (GAA) deficiency by dried blood spot (DBS) investigation. Methods: DBS were collected from 3, 076 consecutive adult patients from 7 German and British neuromuscular centers. All specimens were investigated for GAA deficiency by fluorometry. Samples with reduced enzyme activity were subsequently investigated for GAA gene mutations. Results: Of 3, 076 patients with DBS samples, 232 patients (7.6%) showed low GAA enzyme activity. Of these 232 patients, 55 (24%) presented with isolated hyperCKemia and 176 (76%) with hyperCKemia and LGMW. With both features present, 94% of the patients showed a low enzymatic activity. Mutational analysis found GAA gene mutations in 74 patients (2.4%); herein 70 patients were heterozygote for the common GAA gene splice-site mutation c.-32-13T>G. The most common clinical presentation in the confirmed Pompe cohort was a limb-girdle phenotype (85.3%) combined with ventilatory insufficiency (61%). Isolated hyperCKemia was found in 12%, while 2.7 had hyperCKemia and ventilatory insufficiency only. Conclusions: In a large cohort of unselected adult patients with hyperCKemia and/or LGMW, we found a prevalence of late-onset Pompe disease of 2.4%. Therefore, targeted screening of such a population should be encouraged in clinical practice.